The process of interpretation of signs: a proposal for semiotic analysis for Science Teaching - Favreto, Elemar Kleber (2022)
The application of semiotic analysis in science education is still a process under development in Brazil, requiring not only research in the area, but proposals capable of transforming its main concepts into elements that can help teachers and students in carrying out their interpretations. of scientific signs. This article aims to develop a path of semiotic analysis for the meaning of scientific signs, contributing to student learning, as well as presenting a teaching strategy to favor this semiotic analysis, helping the teacher in the development of their classes. This path of analysis and the teaching-learning strategy are based on the main structure of Peirce's semiotics. This is a purely bibliographical research, which presents and discusses the elements of Peircean semiotics within a proposal that is still theoretical in scope, but which may later unfold into more practical and experimental research.